Platelet Indices as a Predictor of Microvascular Complications in Type 2 Diabetes (Medical Forum Monthly, 2021)
Objective: The study's main goal is to look at platelet indices as an indicator of microvascular complications in people with type 2 diabetes.Study Design: Cross-Sectional StudyPlace and Duration of Study: This study was conducted at the Jinnah Postgraduate Medical Centre in Karachi from Jan, 2019 to June, 2019 for a period of six months.Materials and Methods: A total of 200 diabetic patients, both male and female, were surveyed. The information was gathered using a Performa that included all demographic information, medical background, blood transfusion history, and other relevant information.Results: The information was obtained from 200 patients of both sexes. In total, 200 participants were found to be diabetic, resulting in a 24.6 percent (95 percent CI 21.90 - 27.49) prevalence of the disease in the study population. 31.5 percent of participants (P 0.001) said they had a history of the disease.Conclusion: Adjustments in platelet files are thought to be measurably linked to diabetes and its complexities, according to the findings.